'It wasn't racism; it was more misunderstanding.' White teachers, Latino/a students, and racial battle fatigue. Issue 4 (4th July 2017) - Call-Cummings, Meagan; Martinez, Sylvia
Abstract: This article explores how and why a group of Latino/a high school students identify and explain racism differently over the course of an 18-month participatory action research (PAR) project. To do this we examine what recent scholarship has termed racial microaggressions in what is thought of as the Post-Racial America public school system. Pulling examples from student and teacher interview, focus group, and class discussion data we first examine how these students' teachers conceptualize and talk about racism, cross-racial relationships, and racial misunderstandings, and then we juxtapose that with students' discursive work to make sense of the ways their teachers make their conceptualizations known and/or seen in school. Focusing on the K-12 context, this study finds racial battle fatigue may be why students switch between how they label these aggressions.